Oral Chinese Herbal Medicine plus usual care for diabetic kidney disease: study protocol for a randomized, double-blind, placebo-controlled pilot trial - Liu, Meifang; Di, Yuan Ming; Zhang, Lei; Yang, Lihong; Zhang, La; Chen, Junhui; Wang, Ruobing; Xie, Xiaoning; Lan, Fang; Xie, Liping; Huang, Juan; Zhang, Anthony Lin; et al. (Frontiers in Endocrinology, 2024)
Background Diabetic kidney disease (DKD) has become the leading cause of kidney failure, causing a significant socioeconomic burden worldwide. The usual care for DKD fails to achieve satisfactory effects in delaying the persistent loss of renal function. A Chinese herbal medicine, Tangshen Qushi Formula (TQF), showed preliminary clinical benefits with a sound safety profile for people with stage 2-4 DKD. We present the protocol of an ongoing clinical trial investigating the feasibility, efficacy, and safety of TQF compared to placebo in delaying the progressive decline of renal function for people with stage 2-4 DKD. Methods A mixed methods research design will be used in this study. A randomized, double-blind, placebo-controlled pilot trial will evaluate the feasibility, efficacy, and safety of TQF compared to placebo on kidney function for people with stage 2-4 DKD. An embedded semi-structured interview will explore the acceptability of TQF granules and trial procedures from the participant’s perspective. Sixty eligible participants with stage 2-4 DKD will be randomly allocated to the treatment group (TQF plus usual care) or the control group (TQF placebo plus usual care) at a 1:1 ratio for 48-week treatment and 12-week follow-up. Participants will be assessed every 12 weeks. The feasibility will be assessed as the primary outcome. The changes in the estimated glomerular filtration rate, urinary protein/albumin, renal function, glycemic and lipid markers, renal composite endpoint events, and dampness syndrome of Chinese medicine will be assessed as the efficacy outcomes. Safety outcomes such as liver function, serum potassium, and adverse events will also be evaluated. The data and safety monitoring board will be responsible for the participants’ benefits, the data’s credibility, and the results’ validity. The intent-to-treat and per-protocol analysis will be performed as the primary statistical strategy. Discussion Conducting a rigorously designed pilot trial will be a significant step toward establishing the feasibility and acceptability of TQF and trial design. The study will also provide critical information for future full-scale trial design to further generate new evidence supporting clinical practice for people with stage 2-4 DKD. Trial registration number https://www.chictr.org.cn/, identifier ChiCTR2200062786.